Gender and Tax Incidence of Rural Land Use Fee and Agricultural Income Tax in Ethiopia - Komatsu, Hitomi (World Bank, Washington, DC, 2021)
The rural land use fee and agricultural income tax are major payments for rural landholders in Ethiopia. This paper examines the gender implications of these taxes using tax payment and individual land ownership data from the Ethiopian Socioeconomic Survey 2018/2019. It finds that the rural land use fee and agricultural income tax, which are assessed on the area of landholdings, are regressive. Female-headed- and female adult-only households bear a larger tax burden than male-headed and dual-adult households. Norms limiting women’s role in agriculture and gender agricultural productivity gaps are likely to result in lower consumption and accordingly, a higher tax burden for female-headed households than for male-headed households. Reducing the tax rates for smallholders can diminish the gender difference in tax burdens, but the tax continues to be regressive. This highlights the difficulty of area-based land taxes to be vertically equitable.